Placental transfer and concentrations of cadmium, mercury, lead, and selenium in mothers, newborns, and young children - Chen, Zhu (J Expo Sci Environ Epidemiol, 2014)
There is an emerging hypothesis that exposure to cadmium (Cd), mercury (Hg), lead (Pb), and selenium (Se) in utero and early childhood could have long-term health consequences. However, there are sparse data on early life exposures to these elements in US populations, particularly in urban minority samples. This study measured levels of Cd, Hg, Pb, and Se in 50 paired maternal, umbilical cord, and postnatal blood samples from the Boston Birth Cohort (BBC). Maternal exposure to Cd, Hg, Pb, and Se was 100% detectable in red blood cells (RBCs), and there was a high degree of maternal–fetal transfer of Hg, Pb, and Se. In particular, we found that Hg levels in cord RBCs were 1.5 times higher than those found in the mothers. This study also investigated changes in concentrations of Cd, Hg, Pb, and Se during the first few years of life. We found decreased levels of Hg and Se but elevated Pb levels in early childhood. Finally, this study investigated the association between metal burden and preterm birth and low birthweight. We found significantly higher levels of Hg in maternal and cord plasma and RBCs in preterm or low birthweight births, compared with term or normal birthweight births. In conclusion, this study showed that maternal exposure to these elements was widespread in the BBC, and maternal–fetal transfer was a major source of early life exposure to Hg, Pb, and Se. Our results also suggest that RBCs are better than plasma at reflecting the trans-placental transfer of Hg, Pb, and Se from the mother to the fetus. Our study findings remain to be confirmed in larger studies, and the implications for early screening and interventions of preconception and pregnant mothers and newborns warrant further investigation.